New insights into the interaction between ADP-ribose and human TRPM2 channel - Kühn, Frank J. P. (Biotarget; Vol 1 (November 2017): Biotarget, 2017)
Since adenosine 5'-diphosphoribose (ADPR) has been discovered (1) as stimulus of the human apoptosis-related ion channel transient receptor potential melastatin 2 (TRPM2), the compound has undergone a rapid ascent from being considered a mere spin-off of the cellular energy metabolism to a generally acknowledged important intracellular second messenger.